Treatment of cows with postpartum endometritis and mastitis - Aliev A.Yu.; Magomedov M.Z.; Kabardiev S.Sh.; Aygubova S.A. (Ветеринария и кормление, 2024)
Reproduction of the herd is the basis of the development of livestock farming, therefore the prevention and elimination of animal infertility are one of the most important conditions of increasing of the production of livestock products. Inflammation of the mammary gland and genital tract in cows is currently widespread often appears simultaneously, or one replaces the other. The reasons of the development of these lesions in cows are multifactorial, while contributing and predisposing factors, are often no less important than infectious ones. Bacteriological studies have established, that the main pathogens in cows with a combined course of endometritis and mastitis are, mainly, coccal microflora; the isolated microflora was highly sensitive to ciftiofur. The study of the therapeutic effectiveness of a complex antibacterial drug, which has a combined antimicrobial, uterotonic, anti-inflammatory and general stimulating effects, was carried out on red steppe cows with a combined course of postpartum endometritis and serous mastitis. The drug was administered to cows intramuscularly, in dose 5 ml per 100 kg, once a day, during 3-5 days. Therapeutic effectiveness in the experimental group - 95.5%, which is on 28.8% higher, than in the control, recovery time was on 1.9 days shorter.